An investigation of young Chinese consumers’ purchasing motivations toward luxury products - Cui, Jingyue (2015)
During the past two decades, luxury sector becomes even popular around the world. Especially in China, people tend to have an appetite for luxury products since the early 1990s. Moreover, the Chinese traditional culture also plays an essential role in influencing Chinese consumers’ purchase behaviours. This dissertation endeavours to create an insightful analysis that helps to understand young Chinese consumers’ purchase motivations toward luxury products. The findings suggest that Chinese traditional culture indeed have impact on consumers’ luxury buying motivations. Specifically, under the collectivist culture, Chinese people tend to care much about others; therefore they are willing to enhance their perceived self-image through buying luxury goods. In terms of the conspicuousness, the findings indicate that Chinese consumers tend to purchase luxury goods are more likely to save “face”, rather than indicate their social status. Moreover, compared to male, young Chinese female consumers are largely influenced by their desired reference groups